Finding out about the past - Freeman, Mae Blacker, 1907- (New York : Random House, 1967)
An introduction to archeology, telling about ways archeologists work, dating and care of old objects, and the things archeologists have found and what they have learned from them.
Keywords: Archaeology -- Juvenile literature